Comparison of PCR, Culture, and Serological Tests for Diagnosis of Mycoplasma pneumoniae Respiratory Tract Infection in Children - Dorigo-Zetsma, J. W. (American Society for Microbiology, 1999)
For diagnosis of Mycoplasma pneumoniae infection we compared two rapid tests, PCR and the immunoglobulin M immunofluorescence assay (IgM IFA), with culture and the complement fixation test (CFT), in a prospective study among 92 children with respiratory tract infection and 74 controls. Based on positivity of culture and/or CFT as the diagnostic criterion, nine patients (10%) were diagnosed with M. pneumoniae infection. All patients positive by culture were also positive by PCR. In all controls cultures, PCRs, and serological assays were negative, except in one with a positive IgM IFA. The IgM IFA had a low positive predictive value of 50%. Only a combination of PCR (seven patients) and CFT (seven patients) allowed diagnosis of all cases.